Risk Based Inspection using API RP 580 and DNV RP F116 Towards Free Spanning Pipelines - Iftinaniffah Qonitah; Yoyok Setyo Hadiwidodo; Daniel Mohammad Rosyid (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2021)
The free span that occurs in the subsea pipeline can cause fatigue due to vortex induced vibration and local buckling. From the risk of failure that may occur, a risk-based inspection scheduling required. The 14